Electrochemical detection of 8-hydroxyguanine using screen-printed carbon electrodes modified with carboxy-functionalized multi-walled carbon nanotubes - Jeličová, Marcela; Metelka, Radovan; Pejchal, Jaroslav; Lierová, Anna; Šinkorová, Zuzana (Springer, 2019)
The paper presents the findings of an optimization and validation results of electrochemical detection of 8-hydroxyguanine, a major marker of oxidative stress, using disposable screen-printed carbon electrode (SPCE) modified with carboxy-functionalized multi-walled carbon nanotubes (MWCNTs-COOH). Several types of bare and modified SPCEs were tested and modification with MWCNTs-COOH was found superior in terms of measured current response, level of background currents, and sensitivity in oxidation of 8-hydroxyguanine. The effect of pH and composition of supporting electrolyte on current response and peak potential were also evaluated. Validation parameters were calculated for optimum pH 7 of 0.01moldm(-3) phosphate buffer. The sensor showed the highest sensitivity of 0.0625 mu A dm(3) mu mol(-1) within the linear range 0.3-12 mu moldm(-3) with a limit of detection as low as 0.57 mu moldm(-3). Extended linear range 0.3-240 mu moldm(-3) is feasible with a sensitivity of 0.0523 mu A dm(3) mu mol(-1). Intra-day and inter-day assays within 3days were performed to verify the repeatability of modified screen-printed carbon sensors. Finally, the sensor was utilized for electrochemical monitoring of stability of 8-hydroxyguanine when stored in room temperature, in the refrigerator, or frozen and thawed. [GRAPHICS] .
Elektrochemická detekce 8-hydroxyguaninu s použitím uhlíkových tištěných elektrod modifikovaných vícestěnnými uhlíkovými naotrubičkami s karboxy skupinami
Keywords: 8-Hydroxyguanine; Screen-printed carbon electrode; Multi-walled carbon nanotubes; Differential pulse voltammetry; 8-Hydroxyguanin; Uhlíková tištěná elektroda; Vícestěnné uhlíkové nanotrubičky; Diferenční pulzní voltametrie